Kingdom power: Receiving the power of the promise: A study in the book of Acts - Hayford, Jack W.; (1934-...) (U.S.A., 1993)
Spirit-filled believers will find new resources for understanding the Bible and applying biblical themes to their day-to-day lives in these interactive study guides.
Keywords: Bible -- Acts -- Study and teaching